Creative Pedagogies in Uncertain Times: What is Essential? A Conversation with Paul Gorman of Hidden Giants - Paul Gorman; Beth Cross (University of Aberdeen, School of Education, 2021)
While bringing together this issue it has been inspiring to learn of work at many different points on the globe. There is work here in Scotland that also touches on the themes of the issue. One educator doing such work is Paul Gorman and the company Hidden Giants. Hidden Giants supports learners, teachers and leaders to create the conditions for change that grow cultures which are empowered, agentic, and brave. Working in partnership with schools from across Scotland and in international contexts their aim is to co-create the conditions for meaningful and sustainable change to take place. To understand their approach a bit better, the explanation of the name Hidden Giants is a good place to start: "We acknowledge and work with the giants that lay hidden in our system: things we know but tend to avoid, i.e. the elephants in the room or what lies beneath the iceberg. These things can be difficult to speak about but if we shy away from them, we will never truly reimagine." (Hidden Giants) Conversations and storytelling are very rich sources of reflection that academic practices can squeeze out of the picture. In this feature we attempt to recreate room for them to explore what is happening at the margins here in Scotland that helps us rethink what Art Education can be about.